Development of an Interactive STEM-SSI Website on Organic Chemistry to Enhance Critical Thinking Skills and Scientific Literacy - Ayu Tri Khodizah; Yogo Dwi Prasetyo; Arif Sholahuddin; Rilia Iriani; Lik Tong Tan (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
The need for learning media is contextual, innovative, and relevant to environmental issues, as well as developments in educational technology, are essential in organic chemistry education. Organic chemistry material, which is often considered abstract, needs to be presented in an engaging manner through the integration of STEM-based content, enriched with discussions on current socio-scientific issues (SSI) in the form of an interactive website. This study aimed to develop an interactive website based on the STEM-SSI approach for organic chemistry materials to enhance students' critical thinking skills and scientific literacy. The research method employs the ADDIE model (analysis, design, development, implementation, and evaluation). The research subjects were 35 students divided into experimental (n =18) and control (n = 17) groups. Data were collected using feasibility and practicality questionnaires, and critical thinking and scientific literacy tests. The results show that the developed STEM-SSI website is valid and practical to use, with validity and practicality scores greater than 4.25 (4.67 and 4.78). This study also demonstrates that websites are effective in improving students' critical thinking skills and scientific literacy, with n-gain scores categorized as high (N-gain = 0.73 and 0.77).